Pemberdayaan Kelompok Wanita Tani “Sri Rejeki” Melalui Budidaya Tanaman Sayuran di Bantul, DIY - Ismiasih Ismiasih; Resna Trimerani; Christina Wahyu Ary Dewi; Helmi Afroda (Madani : Indonesian Journal of Civil Society, 2023)
Women have an important role in a family. In supporting their role, many women are active in community organizations, one of which is the Women Farmers Group (KWT). However, KWT is often used only for meeting women without any productive activities. Therefore, through this community service program (PKM), it is hoped that it can raise independence for mothers to have productive. The partner in this PKM activity is KWT "Sri Rejeki" which is located in Bantul Regency. The PKM location was chosen with the consideration that KWT had quite a large yard of land and was not managed properly. Based on the situation analysis, it is known that the partners' problems include: yards that have not been managed properly, the activities of the women who have not been productive, the desire of the partners to provide knowledge and skills to members regarding the cultivation of horticultural. The solution to this problem is to carry out participatory extension and empowerment actions by combining direct practices of cultivation horticultural with modern methods. The type of program carried out is to train KWT members on modern cultivation of horticultural crops. After the activity was completed, an evaluation was carried out that the partner's knowledge, skills in plant cultivation and ability to use the land increased. As for the continuation of this PKM activity, it is hoped that the yard will become a productive garden, and partners will have a creative and productive spirit in utilizing their free time.